Ouvrir la boîte à outils de la recherche numérique - Jean-Christophe Plantin; Laurence MONNOYER-SMITH (Tic & Société)
Digital methods in humanities and social sciences are often presented as disruptive towards existing methods. On the opposite, Noortje Marres claims that online methods are « redistributed » in order to apply to the digital medium. If these methods are not radicaly new, they face important epistemological debates. This article will present three of these debates by focusing on three types of digital research. Digital humanities interrogate the possibilities of a dialogue between sciences and the humanities ; Cultural Analytics challenges the possibility to do research in humanities with large datasets ; digital methods adress the necessity to create new methods to apply to a digital research object. The conclusion will present how the reflexive and experimental nature of these works can benefit to information and communication sciences.